EFEK PENINGKATAN TEMPERATUR PADA PENETRASI RETANNING AGENT KULIT CRUST SAPI ARTIKEL PURE LINING TERHADAP TEAR STRENGTH - Ikah Aryani; Maria Sriwiyanti; Emiliana Anggriyani (Politeknik ATK Yogyakarta, 2019)
This study aims to determine the effect of increasing temperature on penetration of the retanning agent against tear strength. The material used were blue wet lining cowhide (pure lining article), while the equipments used were scales, thickness, HUNI Drum, Cutter, Tank Drum, pH meter (mettlertoledo), Prodomix, Aquamix, Setting out, Staking Crust, Wet Stretcher, and Toggle Wet. The method used was changing the water temperature during washing after neutralization and water on the penetration of the post-tanning process. The water temperature when washing after neutralization and main water at the time of penetration used were 30oC for control, 20oC for the first treatment, and 35oC for the second treatment. The results obtained were significant differences (P<0.05) the value of tear strength in the three treatment results. In the temperature of 35oC for penetration of retanning agent against tear strength gave very optimal results when viewed from customer requirements compared to temperatures of 20oC and 30oC. The temperature of 20oC gave optimal results if it was laboratory compared to temperatures of 30oC and 35oC. The conclusion that can be drawn was that the increase in temperature at the penetration of retanning agent can increase the value of tear strength of pure lining articles